Morphological and chemical plant traits associated with feeding non-preference to adult of Diabrotica speciosa (Coleoptera: Chrysomelidae) in soybean genotypes - Boica Junior, Arlindo Leal [UNESP]; Costa, Eduardo Neves [UNESP]; Souza, Bruno Henrique Sardinha de; Forim, Moacir Rossi; Perlatti, Bruno; Cruz, Mara Cristina Pessoa da [UNESP] (Cambridge Univ Press, 2022)
Diabrotica speciosa is an important pest of several crops in South America, including soybeans. Adults cause severe defoliation in soybean plants, and damage is significant when cotyledons are attacked. This study evaluated feeding non-preference to D. speciosa adults using 10 soybean genotypes, testing (i) 15-day-old whole plants and (ii) leaf disks of 60-day-old plants, through assessments of soybean attractiveness and leaf area consumed (LAC). Foliar contents of flavonoids and nutrients, and leaf trichome density were quantified for potential correlations with soybean resistance to adult of D. speciosa. In the whole young-plant experiment, under free-choice conditions, the lowest LAC was observed in IAC 100 and PI 227687. In no-choice, PI 227687 and IGRA RA 626 RR showed lower LAC than the other genotypes. In the leaf disk test, in free-choice, the genotypes IAC 100, PI 274454, PI 227687, DM 339, and BR 16 were the least preferred by adult of D. speciosa. In no-choice, PI 274454 was one of the least preferred, similarly to IGRA RA 626 RR, Dowling, and PI 227687. In the whole plant experiment, a high rutin content and low amounts of zinc, calcium, sulfur and manganese were associated with less consumption of D. speciosa on leaves of resistant genotypes. In contrast, in the leaf disk test there was a significant influence of trichomes in soybean resistance to the pest. In conclusion, the PI lines herein assessed are also promising sources for developing cultivars resistant to D. speciosa.
Keywords: Bean leaf beetle; Flavonoids; Glycine max; Nutrients; Plant resistance; Trichomes